2021
DOI: 10.1021/acssynbio.1c00229
|View full text |Cite
|
Sign up to set email alerts
|

The Neurospora crassa Inducible Q System Enables Simultaneous Optogenetic Amplification and Inversion in Saccharomyces cerevisiae for Bidirectional Control of Gene Expression

Abstract: Bidirectional optogenetic control of yeast gene expression has great potential for biotechnological applications. Our group has developed optogenetic inverter circuits that activate transcription using darkness, as well as amplifier circuits that reach high expression levels under limited light. However, because both types of circuits harness Gal4p and Gal80p from the galactose (GAL) regulon they cannot be used simultaneously. Here, we apply the Q System, a transcriptional activator/inhibitor system from Neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Importantly, there is already a study demonstrating comparable or even higher metabolite production from optogenetic strains compared to chemical induction at the bioreactor level . Thus, the two-population systemafter improvement at different levelscan represent a tool to overcome challenges of light penetration in high-density cultures, such as recently described optogenetic amplifiers. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, there is already a study demonstrating comparable or even higher metabolite production from optogenetic strains compared to chemical induction at the bioreactor level . Thus, the two-population systemafter improvement at different levelscan represent a tool to overcome challenges of light penetration in high-density cultures, such as recently described optogenetic amplifiers. , …”
Section: Resultsmentioning
confidence: 99%
“…77 Thus, the two-population system�after improvement at different levels�can represent a tool to overcome challenges of light penetration in high-density cultures, such as recently described optogenetic amplifiers. 78,79 Finally, autonomous (A) versions of our synthetic circuit were generated, where each cell is carrying all the building blocks related to light perception, pheromone production, and reporter expression (Figure 6A). Thus, each cell of A strains has the capacity to induce luciferase expression in response to optogenetically produced pheromone.…”
Section: Acs Synthetic Biologymentioning
confidence: 99%
“…[ 39 ] Optogenetic circuits were developed for S. cerevisiae to optimize the production of acetoin, lactic acid and naringenin. [ 38,40,41 ] These examples highlight the current boost in usage of optogenetic tools in biotechnology approaches and demonstrate the potential of optogenetics for a broad application in industrial settings.…”
Section: Discussionmentioning
confidence: 99%
“…[35] A nec- were published that implemented optogenetic tools for biosynthesis processes. [23,[36][37][38][39][40][41] Namely, metabolic engineering with optogenetic expression tools resulted in increased ethanol and isobutanol production in S. cerevisiae. [23] Acetoin production in E. coli cells was optimized by regulating the cell division time period with optogenetic tools.…”
Section: Discussionmentioning
confidence: 99%
“…Moving beyond this two-step cultivation strategy, several recent studies showed that controlling growth versus production in a dynamic manner can further increase production yields 9,10 . Finely controlling the induction of the metabolic pathways leading to production is critical for such "dynamic regulation" 11 strategies.…”
Section: Introductionmentioning
confidence: 99%